(untitled) (European Journal of Mental Health, 2024)
Introduction: Emotional factors are often specified as playing an important role in the context of problematic alcohol use and alcohol addiction. Aims: This study focused on examining the relationship between difficulties in emotion regulation, perceived personal problems, and problematic alcohol use. Methods: 374 participants from the general population in Slovenia and Croatia (34.8% men, 65.2% women) with an average age of 44.28 years (range: 26 to 74 years) completed the Alcohol Use Disorders Identification Test (AUDIT), Individual Problems and Strengths Scale (IPS) and Difficulties in Emotion Regulation Scale – Short Form (DERS-SF). Results: A higher level of problematic alcohol use positively correlated with difficulties in emotion regulation and the assessment of individual problems (p ≤ .010). Multiple linear regression analysis demonstrated that higher AUDIT scores were positively associated with two dimensions of difficulties in emotion regulation: impulse control difficulties (β = 0.22, p = .008) and lack of emotional awareness (β = 0.15, p = .010). Difficulties in emotion regulation completely mediated the effect of individual problems on problematic alcohol use (indirect effect: 0.18, CI [–.06, –.31]; p < .001): higher levels of individual problems contribute to higher levels of problematic alcohol use through the effect of difficulties in emotion regulation. Conclusions: The findings indicate the vulnerability of individuals with difficulties in emotion regulation to problematic alcohol use. Difficulties in emotion regulation are an important factor to consider for understanding the development, maintenance, and treatment of alcoholism and problematic alcohol use.